Simbolisme Motif Batik Kawung Sebagai Element Estetis Interior di Lobby Pullman Hotel Jakarta Pusat - Diana Muliani (Pascasarjana ISBI Bandung, 2019)
The motif of Batik Kawung is being used as aesthetic elements at Pullman Hotel Lobby in Central Jakarta. It is a part of interior design applied in not only cloth materials. The hotel lobby is a public sphere visited by heterogeneous guests from various social classes. This is a qualitative method with semiotic approach. The data are from informants regarding with batik, as well as from archive anddocuments. The collection of data is conducted through interview and observation. The result shows that there are some motifs of batik kawung that cannot be applied exactly as they are since they have their own symbolic meaning. Regarding this, designers designing interior design of Pullman Hotel Lobby should consider the knowledge.Keywords: symbolic, batik kawung, interior aesthetics elements, Pullman Hotel Jakarta Pusat